Improved damper cage design for salient-pole synchronous generators - Nuzzo, Stefano; Degano, Michele; Galea, Michael; Gerada, C.; Gerada, David; Brown, N.L. (Institute of Electrical and Electronics Engineers, 2016)
The benefits of implementing a damper winding in salient-pole, synchronous generators are widely known and well consolidated. It is also well known that such a winding incurs extra losses in the machine due to a number of reasons. In order to improve the overall efficiency and performance of classical salient-pole, wound field, synchronous generators that employ the traditional damper cage, an improved amortisseur winding topology that reduces the inherent loss is proposed and investigated in this paper. This is essential in order to meet modern power quality requirements and to improve the overall performance of such ’classical’ machines. The new topology addresses the requirements for lower loss components without compromising the acceptable values of the output voltage total harmonic distortion and achieves this by having a modulated damper bar pitch. As vessel for studying the proposed concept, a 4MVA, salient-pole, synchronous generator is considered. A finite element model of this machine is first built and then validated against experimental results. The validated model is then used to investigate the proposed concept with an optimal solution being achieved via the implementation of a genetic algorithm optimization tool. Finally, the performance of the optimised machine is compared to the original design both at steady state and transient operating conditions.